2021
DOI: 10.1038/s41430-021-00961-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and COVID19: a bidirectional relationship

Abstract: The advent and rapid spread of the coronavirus disease-2019 (COVID19) pandemic across the world has focused attention on the relationship of commonly occurring comorbidities such as diabetes on the course and outcomes of this infection. While diabetes does not seem to be associated with an increased risk of COVID19 infection per se, it has been clearly demonstrated that the presence of hyperglycemia of any degree predisposes to worse outcomes, such as more severe respiratory involvement, ICU admissions, need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Acute organ injury caused by COVID-19 can cause long-term cardiovascular [ 1083 , 1084 ], pulmonary [ 1085 ], metabolic [ 1086 ], renal [ 1086 ] and neurological [ 1087 ] damage, potentially contributing to chronic conditions that can themselves be risk factors for severe COVID-19 in subsequent infections. COVID-19 can lead to the exacerbation of asthma [ 1088 ] and neurodegenerative disorders (both Parkinson’s and Alzheimer’s disease) [ 1088 ], and increase the risk of developing mental disorders [ 1088 , 1089 ], diabetes [ 1090 , 1091 ], CKD [ 1092 ], hypertension [ 1093 ] and CVD [ 1094 ]. COVID-19 also disturbs metabolic homeostasis, and can result in a low intake of calories and greatly reduced physical activity during hospitalization, which can exacerbate frailty and biological aging [ 586 ].…”
Section: Interactions Between Effectsmentioning
confidence: 99%
“…Acute organ injury caused by COVID-19 can cause long-term cardiovascular [ 1083 , 1084 ], pulmonary [ 1085 ], metabolic [ 1086 ], renal [ 1086 ] and neurological [ 1087 ] damage, potentially contributing to chronic conditions that can themselves be risk factors for severe COVID-19 in subsequent infections. COVID-19 can lead to the exacerbation of asthma [ 1088 ] and neurodegenerative disorders (both Parkinson’s and Alzheimer’s disease) [ 1088 ], and increase the risk of developing mental disorders [ 1088 , 1089 ], diabetes [ 1090 , 1091 ], CKD [ 1092 ], hypertension [ 1093 ] and CVD [ 1094 ]. COVID-19 also disturbs metabolic homeostasis, and can result in a low intake of calories and greatly reduced physical activity during hospitalization, which can exacerbate frailty and biological aging [ 586 ].…”
Section: Interactions Between Effectsmentioning
confidence: 99%
“…Studies have shown DM is an independent predictor of admission to the intensive care unit (ICU), requiring ventilation or mortality in COVID-19. 1 Hyperglycemia is common in the ICU resulting from stress-induced insulin resistance and increased glucose production. Viral-induced hyperglycemia usually persists because of inflammation and activation of the immune system.…”
mentioning
confidence: 99%
“…On the other hand, COVID-19 is associated with new-onset hyperglycemia or diabetes as well as worsening of preexisting diabetes [ 55 , 56 ]. Possible mechanisms of hyperglycemia in COVID-19 are direct virus-mediated beta-cell damage, triggering of beta-cell autoimmunity by the virus, disorganized and exuberant immune response against the virus, which leads to perturbations in glycemic status, and iatrogenic hyperglycemia caused by corticosteroids [ 57 ]. Our study finding is also consistent with these and we found, compared to survivors, nonsurvivor had a higher blood glucose levels at admission.…”
Section: Discussionmentioning
confidence: 99%